Implementasi Manajemen Kearsipan dalam Meningkatkan Administrasi Sekolah : ( Studi Kasus Di SMPN 3 Tembilahan Hulu) - Ali Murtopo; Leli Safitri; Purwanti; Uswatun Hasanah; Wina (Universitas Islam Indragiri, 2025)
This study was conducted to see how the implementation of archival management in improving the administration of SMPN 3 Tembilahan Hulu. Practically, almost all educational institutions have implemented archival management, but in its implementation, each educational institution will be different and have its own provisions. The purpose of archival administration management in this educational institution is so that office work can be carried out properly, neatly in accordance with existing regulations in improving administration. The implementation of management in improving administration at SMPN 3 Tembilahan Hulu can be said to have not been implemented because there is still a lack of competent human resources in the field of archiving, inadequate facilities and infrastructure and unstructured archival procedures so that they have a negative impact on Administrative employees, the negative impacts are slow access to information, student data becomes unsafe, and takes a long time. The solutions that can be done to improve the implementation or implementation of management in improving administrative archiving at SMPN 3 Tembilahan Hulu are to provide training and education to archival staff, provide facilities and infrastructure by completing a comfortable and safe archival room, create clear archival procedure standards